Crustal structure along the Wanzai–Yongchun profile in the Cathaysia Block, Southeast China, constrained by a joint active- and passive-source seismic experiment. Issue 1 (31st May 2022) - Huang, Minfu; Xu, Tao; Lü, Qingtian; Lin, Jiyan; Bai, Zhiming; Deng, Yangfan; Zhang, Yongqian; Badal, José
SUMMARY: Since the Mesozoic, the South China Block (SCB) has experienced multiple episodes of tectonic magmatism accompanied by metallogenesis. To explore the seismic velocity structure of the crust and its connection with mineralization, we constructed a wide-angle reflection and refraction (WARR) profile by deploying 435 short-period seismometers across the Cathaysia Block in Southeast China. Receiver functions and the H–κ stacking method were applied using a reference 2-D velocity model obtained from the analysis of WARR data. Integration of active- and passive-source seismic data enabled us to obtain an image of the crust and the average Vp/Vs ratio value of the SCB and produce several results: (1) The crustal thickness varies west-to-east from 28 km below the Qinhang metallogenic belt to 32 km below the Wuyishan metallogenic belt, and the average value of the Vp/Vs ratio for the crust is 1.71. Both the thickness of the crust and the average Vp/Vs ratio are lower than the average global values for the continental crust. (2) The relatively low Vp/Vs ratio and thin crust along the profile could be generated by thinning of the lower crust in the SCB as a result of the backarc extension related to westward subduction of the Paleo-Pacific plate below East Asia. (3) The Moho depth estimated from H–κ stacking with the help of the background P -wave velocity model modified by the WARR model fits better than using a global seismic velocity model with its common conversion point image, which supports a potential seismic data analysis technique provided with a joint deployment of both active- and passive-source seismic observation system with a shorter period.